Strip tees : a memoir of millennial Los Angeles - Flannery, Kate (Henry Holt and Company, 2023)
"At the turn of the new millennium, LA is the place to be. "Hipster" is a new word on the scene. Lauren Conrad is living her Cinderella story in the "Hills" on millions of television sets across the country. Paris Hilton tells us "That's hot" from behind the biggest sunglasses imaginable, while beautiful teenagers fight and fall in love on The O.C. Into this most glittering of supposed utopias, Kate Flannery arrives with a Seven Sisters diploma in hand and a new job at an upstart clothing company called American Apparel. Kate throws herself into the work, determined to climb the corporate fashion ladder. Having a job at American Apparel also means being a part of the advertising campaigns themselves, stripping down in the name of feminism. She slowly begins to lose herself in a landscape of rowdy sex-positivity, racy photo shoots, and a cultlike devotion to the unorthodox CEO and founder of the brand. The line between sexual liberation and exploitation quickly grows hazy, leading Kate to question the company's ethics and wrestle with her own. Strip Tees captures a moment in our recent past that's already sepia toned in nostalgia, and also paints a timeless portrait of a young woman who must choose between what business demands and self-respect requires"--